2014
DOI: 10.1038/srep05421
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia telangiectasia derived iPS cells show preserved x-ray sensitivity and decreased chromosomal instability

Abstract: Ataxia telangiectasia is a neurodegenerative inherited disease with chromosomal instability and hypersensitivity to ionizing radiation. iPS cells lacking ATM (AT-iPS cells) exhibited hypersensitivity to X-ray irradiation, one of the characteristics of the disease. While parental ataxia telangiectasia cells exhibited significant chromosomal abnormalities, AT-iPS cells did not show any chromosomal instability in vitro for at least 80 passages (560 days). Whole exome analysis also showed a comparable nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
1
33
1
Order By: Relevance
“…We were not able to detect any consistently up or downregulated genes or pathways in pluripotent state between A-T iPSCs and iPSCs generated from healthy donor fibroblasts (WT iPSCs). These data show that ATM deficiency does not affect global gene expression in the pluripotent state, similar to previous reports [21][22][23][24].…”
Section: Ipscs With Deficiencies In Atmsupporting
confidence: 80%
See 1 more Smart Citation
“…We were not able to detect any consistently up or downregulated genes or pathways in pluripotent state between A-T iPSCs and iPSCs generated from healthy donor fibroblasts (WT iPSCs). These data show that ATM deficiency does not affect global gene expression in the pluripotent state, similar to previous reports [21][22][23][24].…”
Section: Ipscs With Deficiencies In Atmsupporting
confidence: 80%
“…Mutations in ATM result in defective cell cycle checkpoint activation and a reduced capacity for repair of DNA double-strand breaks (DSBs). iPSCs from A-T patients have been generated by multiple laboratories, but the issue of genomic variation has not been comprehensively investigated [20][21][22][23][24]. We analyze the CNVs of iPSCs derived from A-T patient using high-resolution single-nucleotide polymorphism (SNP) array and discovered differential genome-wide distribution relative to replication timing organization and the effects of integrating versus nonintegrating reprogramming methods.…”
mentioning
confidence: 99%
“…γ‐H2A.X recruits Mbc1 at the site of the break and triggers DNA repair by recruiting the HR repair machinery including Brca1, Brca2, Rad51, and 53BP. Supporting the central role of p53 in eliminating DNA‐damaged cells during reprogramming, MEFs deficient in either Atm or 53BP1 show a decrease in reprogramming efficiency . Moreover, HR DNA DSB repair genes such as Brca1, Brca2, and Rad51, Fanconi anemia genes involved in both DNA DSB repair and interstrand cross‐link processing, and nonhomologous end joining DSB repair genes have all been shown to be required for efficient reprogramming to a pluripotent state.…”
Section: A Functional Dissection Of the Reprogramming Processmentioning
confidence: 95%
“…Medulloblastoma forms in similar phenotype and anatomical location by haploinsufficiency of ptch1 in mice, but do not exhibit loss of heterozygosity (6,7). Human disease-specific induced pluripotent stem cell (iPSC) has been used as one of human disease models to complement animal models (8,9). Basic schemes how to utilize patient iPSCs for disease mechanism studies have been well demonstrated (10,11).…”
Section: Introductionmentioning
confidence: 99%